Occurrence and assessment of chronic pain fatigue and sleep disturbance in axial spondyloarthritis patients - Eman Abdel Ghani Sayed; Samer Samy; Faruk Ali Abdi; Anna Abou-Raya (Alexandria Journal of Medicine, 2025)
Background Axial spondyloarthritis is an inflammatory arthritis with low back pain that affects the axial skeleton and sacroiliac joints, with extra-articular manifestations. Features of axSpA include pain, stiffness, reduced mobility, fatigue, and sleep disturbance. Fatigue has a strong link to sleep disorders, disease determining parameters, and poor psychological status. Fatigue and sleep disturbance induced by inflammatory pain affect the health-related quality of life.Objectives To determine the occurrence of chronic pain, fatigue, sleep disturbance in axSpA, and their influence on the health-related quality of life.Patients Forty patients with axSpA were diagnosed according to Spondyloarthritis International Society (ASAS) classification criteria. Patients with rheumatoid arthritis, cancer, liver disease, and severe sleep or psychiatric disorders were excluded.Methods Complete blood count, erythrocyte sedimentation rate, C-reactive protein (CRP), human leucocyticantigen-B27, plain x-ray, and magnetic resonance imaging of the sacroiliac joints were performed. Functional scores, patient index data, axial SpA disease activity index, perceived stress scale, hospital anxiety and depression scale, functional axial SpA index, Pittsburgh sleep quality index, visual analogue scale, health assessment questionnaire, euro level QoL-5 dimension-3 L, work limitation questionnaire, fatigue item of the BAS-DAI, and fatigue severity scale were analyzed.Results Elevated levels of ESR (19.08 ± 11.75) and CRP (10.28 ± 6.29) were highly associated with chronic pain and discomfort in axSpA. ESR (p = 0.001), CRP (p = 0.001), and PAPID3 (p = 0.001) showed a significant positive correlation. ASDAS (p = 0.014), PSS (p = 0.015), RAPID3 (p = 0.015), and HADS (p = 0.011) were highly related to sleep disturbance and were statistically significant. The relationship between fatigue, age, BMI, CRP, ESR, PSS, and HADS was not statistically significant.Conclusion The increased occurrence of sleep disorders, anxiety, depression, fatigue, and chronic pain and elevated ESR, CRP, HLA-B27, and disease activity scores with lowered QoL explain the association of these factors with disease comorbidities. Additionally, more support and appropriate management of axSpA would be necessary to prevent sleep disorders and their associated complications.